Analisis Nilai-Nilai Moral dalam Lirik Lagu Daerah Nias “Ae Halödo Paci dan Lato-Lato” Karya Markus Halawa - Sukardi Hulu; Miseri Cordias Palamarta Gulo; Boy Damai Putra Zega; Noveri Amal Jaya Harefa (Departement of Mathematics Education, 2024)
The purpose of the research is to describe the meaning and moral values contained in the lyrics of Nias folk songs